Mouse antibody to phosphocholine can protect mice from infection with mouse-virulent human isolates of Streptococcus pneumoniae. - Briles, D E (1992)
Previous studies have demonstrated that mouse antibodies to phosphocholine (PC) can protect mice against fatal infection caused by several, but not all, mouse-virulent laboratory strains of Streptococcus pneumoniae. Because the pneumococcal strains used in previous studies had been mouse passed and were propagated for many years outside of humans, it was not known whether antibody to PC would be able to protect mice against S. pneumoniae freshly isolated from humans. In the present study, we examined the ability of an immunoglobulin G (IgG) monoclonal antibody (MAb) to PC to protect against infections in mice caused by 14 pneumococcal strains of capsular types 3, 4, 6A, and 6B. Nine of these strains were selected as the most virulent strains for mice from a group of 69 fresh clinical isolates. Five were mouse-passed laboratory strains. Mouse IgG3 MAb to PC was able to exhibit protective effects (survival or increased time to death) against infection with virtually all of the strains injected intravenously and against infection with 70% of the strains injected intraperitoneally. The protective effects of antibody to PC appeared to be partially dependent on capsular type. MAb to PC was most effective against capsular type 3 strains and least effective against type 4 strains. With type 3 and type 4 strains, MAb to PC could frequently protect against larger numbers of CFU injected intravenously than intraperitoneally. For capsular type 6A and 6B strains the reverse was true.